LE STYLE NATIONAL DANS LES ŒUVRES DE L’OPÉRA ROUMAIN EN TRANSYLVANIE PENDANT LA PÉRIODE ENTRE LES DEUX GUERRES - Otilia Maria CONSTANTINIU (Studia Universitatis Babeş-Bolyai. Musica)
The central idea of this study concerns the national identity in the operas of the Romanian composers from Transylvania during the interwar decades when Romanian intellectuality was concerned with the definition and redefinition of the culture of a recently made geopolitical entity and with the protection of this national „being” from protesters. National specificity, as a romantic heritage influenced by the herderian thinking, was an inspirational source in configuring the idea of authenticity, in this equation the main characters being the national language and the folksong. When a series of symbols and other particular aspects to nation like national history with its legendary heroes are attached to this characteristic features to the national Romanian culture, they find a favorable environment in the opera genre. When the opera is stimulated by an institution placed under the state patronage that leads into a national direction, the music resulted is conditioned by the external parameters. In the same time, this music must respond to the demand of aligning its language to the modernist techniques. The responsibility faced to the national personalization of the musical style and language that also had to keep an universal relevance, was a reaction of the interwar Romanian composers confronted almost simultaneously with what meant to be the shaping of the Romanian musical school of composition.